Treatment of produced water from Niger Delta oil fields using sequential mixture of bio-adsorbents. Issue 1 (1st January 2021) - Udeagbara, S.G; Isehunwa, S.O; Okereke, N.U; Oguamah, I. U; Kerunwa, A; Nwanwe, O.
Abstract: Produced water (PW) exploited from the reservoir alongside oil often contains heavy metals and other impurities that are harmful to man and the environment. Most of the PW treatment technologies that have been in use for years have been reported to be ineffective in reducing some of the impurities and metal concentrations to allowable disposal levels. This study evaluated the effectiveness of four local materials combined for treating PW from Niger Delta oil fields. Orange peels (I), banana peels (II), sponge gourd ( Luffa cylindrica) (III) and palm kernel fibers (IV) were washed with distilled water, sun-dried (24 hours) and oven-dried at 105 ± 5°C (3 hours, I and II), 150°C (30 minutes, III) and 80°C (3 hours, IV). They were ground into powder, sieved (150 microns, Group A) and (300 mcicrons, Group B), washed with 0.4 mol/L HNO3, filtered and rinsed with distilled water. Samples of PW were obtained from fields R, X, and Y in the Niger Delta and analyzed for heavy metals using an Atomic Absorption Spectrophotometer (AAS). The PW samples were treated with the bio-adsorbents sequentially in the adsorption column for over 7 hours. Langmuir and Freundlich models were used to evaluate the samples and the Data was analyzed based on regression method. The 150 micron size of sample R, lead (Pb), cadmium (Cd), copper (Cu), and chromium (Cr) were completely (100%) adsorbed from the PW after 8 hours of treatment while other metals (Ni, Fe, Mg, Zn, Mn, Ca, Ar, B, Sn, Ba) were found to be 86.11%, 90.76%, 39.25%, 94.40%, 43.55%, 99.26%, 54.62%, 44.53%, 84.52%, and 47.37%, respectively. while the reduction in 300 micron size were 23.48% for Pb, 80.20% for Ni, 71.42% for Cd, 19.73%, for Cu. 43.65% for Fe, 34.79% for Mg, 12.67% for Cr, 88.8% for Zn, 35.48% for Mn, 98.95% for Ca, 23.01% for Ar, 44.52% for B, 14.83% for Sn and 23.68% for Ba, respectively. The finer adsorbent with large surface area was more effective. Similar results were obtained for PW samples from the other fields. Sequential mixture of the bio-adsorbents selected proved valuable in the treatment of contaminants in PW from Niger Delta oil fields.